Logistics as an essential area for the development of the solid waste management in Colombia - Colorado-Lopera, Diana; Echeverry-Lopera, Gloria Inés; Colorado-Lopera, Henry (Informador Técnico, 2019)
This research summarizes findings of solid waste logistics not only in Colombia, but in other Latin American countries with reference to some of the leading economies throughout the world. All official data and new results are developed and discussed, providing an account for the evolution of solid waste and its logistics regarding time with a focus on transportation and storage. The study also refers to the transportation of waste and its storage in landfills. Due to the situation in Colombia is quite similar to many developing countries, the findings of this study might be of interest to other nations. Results revealed several problems involving the economy, technology, regulations, and political concerns common to several countries worldwide.